Terapi Musik terhadap Efikasi Diri pada Pasien Kanker - Indah Susilowati; Dewi Gayatri; Tuti Nuraini (Jurnal Keperawatan Silampari, 2023)
This study aims to determine music therapy intervention's role in cancer patient's self-efficacy. The research method used was a systematic review of several journals reporting music therapy's effects on cancer patients' self-efficacy. A total of 9 studies met the requirements for consideration, including 9 designs, namely quasi-experimental (3 studies), randomized control trials (2 studies), non-randomized control (1 study), and cross-sectional (1 study). The results showed 671 respondents from the nine studies analyzed in this systematic review. We found the effect of music therapy intervention on cancer patient's self-efficacy. In conclusion, this review provides strong evidence regarding the impact of music therapy, namely increasing self-education. Music therapy intervention can be carried out with active and passive music therapy, which affects patient self-efficacy, especially in cancer patients. Keywords: Self-Efficacy, Cancer Patients, Music Therapy